Perancangan Trainer Komunikasi Receiver Frequency Modulation sebagai Media Pembelajaran untuk Teknik Elektro - Rahmawati, Diana; Ubaidillah, Achmad; Wahyuni, Ardian (Rekayasa, 2021)
On a Frequency Modulation (FM) receiver there is an interference caused which is usually due to the distance and strong signal from the FM transmitter carried to the FM receiver device. The system used PLL (Phase Loocked Loop) system on the oscillator. An oscillator is an electronic device that produces a voltage signal output. The use of oscillators as the carrier of the signal and the message signal produces waves with a certain frequency value, and has a frequency shift of 56,25KHz. The output of the FM receiver is a signal containing of the FM transmitter in the 88MHz-108MHz range. The signals received from the transmitter are short audio and sine signals, so they can be analyzed based on their waves in oscilloscopes and matlab experiments. In this trainer, there are tuners, IF amplifier, multiplexer demodulator, and digital counter frequency. The IC used is LA1260, LA3361, LB3500, LC7265. The result of making an FM receiver trainer get a satisfaction value of the practical test 80,12% based on aspects of media appearance, technical quality and usefulness. A device designed for UTM Electrical Engineering students as a trainer in FM telecommunications system learning medium practiced in the UTM Department of Electrical Engineering